2016
DOI: 10.1248/bpb.b16-00113
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microneedles to Skin Induces Activation of Epidermal Langerhans Cells and Dermal Dendritic Cells in Mice

Abstract: An adequate immune response to percutaneous vaccine application is generated by delivery of sufficient amounts of antigen to skin and by administration of toxin adjuvants or invasive skin abrasion that leads to an adjuvant effect. Microneedles penetrate the stratum corneum, the outermost layer of the skin, and enable direct delivery of vaccines from the surface into the skin, where immunocompetent dendritic cells are densely distributed. However, whether the application of microneedles to the skin activates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…To date, the mechanisms behind this therapy remain undefined; several studies have indicated that AHP took part in the immunological regulation when treating allergic rhinitis and asthma [ 14 , 15 ]. With an increasing understanding of the skin as an immune system, the intradermal route has emerged as an ideal route to administer vaccines and immunomodulators [ 16 ]. Strong associations were observed between skin reactions and therapeutic efficacy by researchers [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the mechanisms behind this therapy remain undefined; several studies have indicated that AHP took part in the immunological regulation when treating allergic rhinitis and asthma [ 14 , 15 ]. With an increasing understanding of the skin as an immune system, the intradermal route has emerged as an ideal route to administer vaccines and immunomodulators [ 16 ]. Strong associations were observed between skin reactions and therapeutic efficacy by researchers [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prow et al ( 2010 ) have visualized MN-induced migration of thousands of antigen presenting cells (APCs) in epidermal area of mice after activating with a conventional antigen or DNA vaccine through MN application (Prow et al 2010 ). In addition to serving as a delivery system, MN system may serve as a physical adjuvant by increasing cell death-induced immunity during application (Depelsenaire et al 2014 ; Takeuchi et al 2016 ). Furthermore, because of its benefits of stability and simplicity, using MN is considered as a practical and efficient method for nucleic acid vaccination.…”
Section: Microneedles For Nucleic Acid Deliverymentioning
confidence: 99%
“…In our previous study, we demonstrated that physically stimulating the skin with MNs effectively activated LCs in C57BL/6 mice. [ 5 ] Given that MNs have been used for delivering drugs, including large molecules like antigens, to the skin, drug delivery techniques studied extensively enable effective vaccination to be utilized. [ 2 6 ]…”
Section: Introductionmentioning
confidence: 99%